Temperature effect on acoustic plasmons; Physical Review B; Vol. 94, iss. 16 - Silkin V. M. Vyacheslav Mikhaylovich; Nazarov V. U.; Balassis A.; Chernov I. P. Ivan Petrovich; Chulkov E. V. Evgeny Vladimirovich (2016, 2016)
Title screen